PROMOSI UNTUK MENINGKATKAN PENDAPATAN PRODUK SURAT DAN PAKET PADA PT POS INDONESIA (PERSERO) BANJARMASIN - Sri Mulyani; Diana Hayati; Hasbiannur Hasbiannur (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2019)
Abstract, The research aims analyze promotions to increase revenue for mail and package products at PT Pos Indonesia (Persero) Banjarmasin. The method used is descriptive method. The research population was customers of PT Pos Indonesia (Persero) Banjarmasin in 2017, 1440 customer people. The research sample uses the Slovin formula to 100 customers. The conclusion of this research is the promotion of PT Pos Indonesia (Persero) Banjarmasin in increasing its customers so far not yet promoting the promotion of services to the maximum. The services offered to customers and companies have not yet optimized their marketing steps through promotion of service product sales